Socio-economic and ecological outcomes of community based forest management: A case study from Tobé-Kpobidon forest in Benin, Western Africa. - Gbedomon, Rodrigue Castro; Floquet, Anne; MONGBO, Roch; SALAKO, Kolawolé Valère; Fandohan, Adandé Belarmain; ASSOGBADJO, ACHILLE EPHREM; Glèlè Kakaї, Romain Lucas (My University, 2016)
Community forestry, promoted as a “win–win” forest management strategy yielded a variety of results that includes both failure and relative success. The willingness of government to hold control over forest resources while transferring only part of property rights to local communities is one of the major constraints. Therefore, there is a need to explore alternative approaches, which enhance the position and accountability of local communities in community forest management. This study evaluated socio-economic and ecological outcomes of community forestry in a context of important property rights conceded to local communities. The study was conducted using focus groups discussions, forest income evaluation and assessment of forest resources and their dynamics. Findings showed that institutional design with important property rights conceded to local communities partially empowered local communities and reduced threats while improving the condition of forest resources. The approach also yielded positive economic outcomes that enabled bordering populations to make up to 25% of their global annual income from the forest. However, the sustainability of this scheme of forest management was mostly limited by the financial dependency on local non-governmental organization, by local institutions and discrepancy in forest benefits sharing among local forest users.
Keywords: Community forestry; Traditional institutions; Socio-economic and ecological outcomes; Benin